PENGARUH MOTIVASI KERJA DAN KOMPETENSI GURU TERHADAP KINERJA GURU DIMODERASI KEPEMIMPINAN TRANSFORMASIONAL STUDI KASUS PADA GURU MADRASAH ALIYAH DI KECAMATAN WINONG KABUPATEN PATI - Endah Susilowati, 12.52.02.0215; Suhari, Yohannes (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aims to examine and analyze whether the effect of work motivation and teacher competence on teacher performance transformational leadership moderated Principal at Madrasah Aliyah teacher in District Winong Pati regency. Sampling was done by census method so that all teachers who worked in Madrasah Aliyah in District Winong of Pati regency, amounting to 83 people as respondents. Mechanical testing of the data used in this study include testing the validity of the factor analysis, reliability testing with Cronbach alpha formula, multiple regression analysis, and the significance test, the coefficient of determination to prove the truth of the hypothesis of research and testing moderation. The results showed that; work motivation has positive and significant effect on teachers performance, teacher competence has positive and significant impact on teacher performance, transformational leadership has positive and significant impact on teacher performance, the effect work motivation on teachers performance moderated by transformational leadership, and the influence of teacher competence on teachersâ performance moderated by transformational leadership at Madrasah Aliyah in District Winong of Pati regency. Keywords: work motivation, teacher competence, transformational leadership, teacher performance